The Role of Location Accessibility and Servicescape in Shaping Customer Satisfaction and Loyalty: Evidence from Traditional Food Microenterprise - Yudha Tama, Firgiawan; Helmy Kusuma, Mochamad; Wilar Mahinda, Razan; Alifianti Rusyana, Vivin; Citra Paramita, Zhafira; Indriani Pratami, Eggi; Rafdinal, Wahyu (Jurnal Manajemen, 2025)
This study investigates how location accessibility and the quality of the physical service environment (servicescape) shape perceived value for money, customer satisfaction, and customer loyalty within traditional micro-scale culinary businesses, particularly warung soto.The intensifying competition in the food industry has increased the importance of creating meaningful dining experiences, making both spatial accessibility and environmental design crucial determinants of customer evaluations. A quantitative research design was employed by distributing an online questionnaire to 100 individuals who had previously visited a warung soto. The data were analyzed using the SEM-PLS approach via SmartPLS 4.0 to assess measurement validity, construct reliability, and the structural relationships among variables. The findings reveal that both location accessibility and servicescape exert significant positive effects on perceived value for money and customer satisfaction. Furthermore, perceived value for money enhances customer satisfaction but does not directly lead to customer loyalty, indicating that positive value perceptions must be accompanied by satisfying experiences to encourage repeat patronage. In contrast, customer satisfaction emerged as the strongest predictor of customer loyalty, emphasizing that a consistently positive dining experience is essential for building long-term commitment. Overall, the study highlights the strategic importance of enhancing accessibility, improving physical service environments, and ensuring pleasant customer experiences to strengthen perceived value and foster loyalty within traditional micro food enterprises. Future research is encouraged to broaden the scope of variables and contexts to enrich insights into consumer behavior in the culinary sector.